In vivo electrical conductivity of hepatic tumours - Haemmerich, Dieter; Staelin, S. T.; Tsai, J. Z.; Tungjitkusolmun, S.; Mahvi, D. M.; Webster, J. G. (My University, 2003)
Knowledge of electrical tissue conductivity is necessary to determine deposition of electromagnetic energy and can further be used to diagnostically differentiate between normal and neoplastic tissue. We measured 17 rats with a total of 24 tumours of the K12/TRb rat colon cancer cell line. In each animal we measured in vivo hepatic tumour and normal tissue conductivity at seven frequencies from 10 Hz to 1 MHz, at different tumour stages between 6 and 12 weeks after induction. Conductivity of normal liver tissue was 1.26 ± 0.15 mS cm-1 at 10 Hz, and 4.61 ± 0.42 mS cm-1 at 1 MHz. Conductivity of tumour was 2.69 ± 0.91 mS cm-1 at 10 Hz, and 5.23 ± 0.82 mS cm-1 at 1 MHz. Conductivity was significantly different between normal and tumour tissue (p < 0.05). We determined the percentage of necrosis and fibrosis at the measurement site. We fitted the conductivity data to the Cole-Cole model. For the tumour data we determined Spearman's correlation coefficients between the Cole-Cole parameters and age, necrosis, fibrosis and tumour volume and found significant correlation between necrosis and the Cole-Cole parameters (p < 0.05). We conclude that necrosis within the tumour and the associated membrane breakdown is likely responsible for the observed change in conductivity.
Keywords: Electrical properties; Tissue conductivity; Tumour conductivity